2016
DOI: 10.1016/j.nut.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with curcumin on serum adipokine concentrations: A randomized controlled trial

Abstract: Curcumin can improve serum levels of adiponectin and leptin in patients with metabolic syndrome. This trial was registered at the UMIN Clinical Trials Registry (http://www.umin.ac.jp/ctr/) under Trial No. UMIN000018339.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 61 publications
(65 reference statements)
2
69
1
2
Order By: Relevance
“…Leptin activates inflammatory cytokine release, including IL-1a, IL-1b, IL-6, and TNF-α, that in turn modulates the immune response (Lord et al, 1998). Adiponectin and gherelin are also important in appetite and energy homeostais, and curcumin has been shown to cause adipokine release from adipocytes (Panahi et al, 2016b), inducing lipolysis that may affect leptin (Song and Choi, 2016). It has been suggested that curcumin may increase ghrelin levels through its antioxidant actions (Xu et al, 2013); however, how curcumin modulates the interplay between leptin, adiponectin, and gherelin needs clarification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin activates inflammatory cytokine release, including IL-1a, IL-1b, IL-6, and TNF-α, that in turn modulates the immune response (Lord et al, 1998). Adiponectin and gherelin are also important in appetite and energy homeostais, and curcumin has been shown to cause adipokine release from adipocytes (Panahi et al, 2016b), inducing lipolysis that may affect leptin (Song and Choi, 2016). It has been suggested that curcumin may increase ghrelin levels through its antioxidant actions (Xu et al, 2013); however, how curcumin modulates the interplay between leptin, adiponectin, and gherelin needs clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Investigative clinical trials have suggested that curcumin has antioxidant (Panahi et al, 2016a;Sahebkar et al, 2015b), antiinflammatory (Panahi et al, 2012;Sahebkar, 2014a), and immunomodulatory (Ghandadi and Sahebkar, 2017;Karimian et al, 2017;Ganjali et al, 2014) properties and is effective in a wide number of diverse conditions including osteoarthritis and rheumatoid arthritis (Kurien et al, 2015;Panahi et al, 2014c;Sahebkar and Henrotin, 2016), metabolic syndrome (Inzaugarat et al, 2017;Panahi et al, 2015b;Panahi et al, 2014b;Sahebkar, 2013;Rahmani et al, 2016), cancer (Deng et al, 2016;Teymouri et al, 2017;Mirzaei et al, 2016;Momtazi et al, 2016), dyslipidemia (Panahi et al, 2016c;Sahebkar, 2014b;Ganjali et al, 2017), chronic obstructive pulmonary disease (Lelli et al, 2017;Panahi et al, 2014a), and anxiety and depression (Esmaily et al, 2015;Panahi et al, 2015a). Curcumin has a direct effect on adipokine release from adipocytes (Panahi et al, 2016b;Hajavi et al, 2017) with the suggestion that it may induce lipolysis and regulate leptin in animals (Song and Choi, 2016). Data suggest that there is an effect on leptin receptor gene expression (Nejati-Koshki et al, 2014b;Nejati-Koshki et al, 2014a) and that interruption of the leptin signaling pathway with a fall in leptin levels decreases advanced glycation end-products (Tang and Chen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…alcoholic fatty liver disease [17,18], atherosclerosis [19,20], chronic complications due to sulfur mustard intoxication [21][22][23][24], solid tumors [25], colorectal cancer [26] and inflammation [27,28]. Several in vitro and animal studies have revealed the inhibitory effect of curcumin on H. pylori [29][30][31][32][33][34][35][36][37], however clinical studies evaluating the efficacy of curcumin supplementation in PU have been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it leads to insulin resistance and mitochondrial injury (Pérez-Matute, Pérez-Martínez, Blanco, & Oteo, 2013). Curcumin (Curcuma longa L.) supplementation stands out as a promising strategy to minimize some of the ART side effects, because it has antioxidant, antiinflammatory, antithrombotic, and hepatoprotective effects (Panahi et al, 2016). Curcumin seems to modulate the expression of genes and the activity of enzymes involved in the lipid homeostasis (Mohammadi et al, 2013) and to have a glucose-lowering effect (Na et al, 2013).…”
Section: Introductionmentioning
confidence: 99%